Boosting customer loyalty by increasing brand engagement and offering value-added solutions: the value added of a loyalty program - Salvador, Bernardo Santiago De Carvalho (2022)
The Consulting Project focuses on the strategic assessment of the potential value creation of a loyalty program in the context of the insurance industry and also on the development of one for Tranquilidade–including its value proposition; structure; mechanics; and financial impact assessment. The fulfilment of this pair of objectives was accomplished by conducting external and internal analyses, in order to identify not only the opportunities and threats in the insurance industry but also to pin point Tranquilidade’s strengths and weaknesses to succeedinit. The Team proceeded to formulate hypotheses and testing them ,by interviewing experts in the industry; doing in-depth interviews with customers; doing a survey; and organizing two focus groups as well as one design-thinking workshop. The outcome of the present project is a loyalty program–the + Tranquilos Program–,as a main recommendation, along side asetof additional considerations, whose implementation will be critical to the success of the Program, aligned with the project’s title: “Boosting Customer Loyalty by Increasing Brand Engagement and Offering Value-added Solutions”, so that Tranquilidade can become a life time partner for Portuguese insurance customers.